Current Challenges for IDO2 as Target in Cancer Immunotherapy - Mondanelli, Giada; Mandarano, Martina; Belladonna, Maria Laura; Suvieri, Chiara; Pelliccia, Cristina; Bellezza, Guido; Sidoni, Angelo; Carvalho, Agostinho; Grohmann, Ursula; Volpi, Claudia (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors have revolutionized the clinical approach of untreatable tumors and brought a breath of fresh air in cancer immunotherapy. However, the therapeutic effects of these drugs only cover a minority of patients and alternative immunotherapeutic targets are required. Metabolism of L-tryptophan (Trp) via the kynurenine pathway represents an important immune checkpoint mechanism that controls adaptive immunity and dampens exaggerated inflammation. Indoleamine 2,3-dioxygenase 1 (IDO1), the enzyme catalyzing the first, rate–limiting step of the pathway, is expressed in several human tumors and IDO1 catalytic inhibitors have reached phase III clinical trials, unfortunately with disappointing results. Although much less studied, the IDO1 paralog IDO2 may represent a valid alternative as drug target in cancer immunotherapy. Accumulating evidence indicates that IDO2 is much less effective than IDO1 in metabolizing Trp and its functions are rather the consequence of interaction with other, still undefined proteins that may vary in distinct inflammatory and neoplastic contexts. As a matter of fact, the expression of IDO2 gene variants is protective in PDAC but increases the risk of developing tumor in NSCLC patients. Therefore, the definition of the IDO2 interactome and function in distinct neoplasia may open innovative avenues of therapeutic interventions.